Ten years of tropospheric ozone from DSCOVR EPIC: science and applications - Ziemke, Jerry R.; Kramarova, Natalya A.; Frith, Stacey M.; Huang, Kai-Liang; Baek, Kanghyun; Herman, Jay R. (Frontiers in Remote Sensing, 2025)
The Earth Polychromatic Imaging Camera (EPIC) onboard the Deep Space Climate Observatory (DSCOVR) spacecraft has enabled near-global measurements of total ozone, SO2, aerosols, surface reflectivity, surface UV, and cloud pressure from June 2015 to the present at high spatiotemporal resolution. The EPIC instrument measures these geophysical parameters synoptically over the entire sunlit disk of the Earth every 1–2 h each day at a resolution down to ∼18 km × 18 km at the nadir sub-satellite point. No current satellite instruments other than EPIC make measurements every 1–2 h over the sunlit disk of the Earth while still obtaining near-global coverage each day. We present scientific results from 10 years of tropospheric column ozone (TCO) data derived from combined EPIC and Modern-Era Retrospective analysis for Research and Applications-2 (MERRA-2) ozone data. We use the EPIC TCO to characterize variabilities in tropospheric ozone from daily to decadal timescales. We also use EPIC TCO with hourly sampling to evaluate the geostationary measurements of total and tropospheric ozone from the Geostationary Environmental Monitoring Spectrometer (GEMS) instrument. The EPIC TCO hourly data gridded at 1o × 1o horizontal resolution for June 2015–present are made available to the general public from the NASA Langley Atmospheric Science Data Center (ASDC) data portal.